2018
DOI: 10.1002/jbmr.3574
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Insulin Resistance in Men Is Associated With Suppressed Undercarboxylated Osteocalcin

Abstract: In mice, glucocorticoid-induced insulin resistance occurs largely through impaired osteoblast function and decreased circulating undercarboxylated osteocalcin (ucOC). Whether these mechanisms contribute to glucocorticoid-induced insulin resistance in humans has yet to be established. In addition, the effects of glucocorticoids on the exercise-induced increase in circulating ucOC and insulin sensitivity are also unknown. We hypothesized that acute glucocorticoid treatment would lead to basal and postexercise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
5
25
1
Order By: Relevance
“…Short‐term use of GCs in the clinical setting has been suggested to induce muscle insulin resistance via the reduction of ucOC . In support, we found that short‐term (3‐days) CS administration is sufficient to suppress circulating levels of both OC and ucOC.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Short‐term use of GCs in the clinical setting has been suggested to induce muscle insulin resistance via the reduction of ucOC . In support, we found that short‐term (3‐days) CS administration is sufficient to suppress circulating levels of both OC and ucOC.…”
Section: Discussionsupporting
confidence: 79%
“…ucOC administration not only enhances muscle insulin sensitivity in healthy animals, but also partially restores insulin sensitivity in insulin‐resistant animals that commonly exhibit low ucOC levels . We recently reported that acute GC‐induced insulin resistance in humans (20 mg of prednisolone) strongly correlated with suppressed serum ucOC and ucOC‐associated signaling pathways in muscle . Furthermore, it has also been reported that the restoration of circulating ucOC during CS administration, via heterotopic expression, rescues whole‐body insulin resistance in mice .…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations